Is previous radical prostatectomy an adversity for laparoscopic total extraperitoneal approach for inguinal hernia repair? A propensity score case matched study - Bilgin, İsmail Ahmet; Ramoğlu, Nur; Özben, Volkan; Çebi, Orkun Harun; Argun, Ömer Burak; Doğanca, Tunkut Salim; Kural, Ali Rıza; Baca, Bilgi; Hamzaoğlu, İsmail; Karahasanoğlu, Tayfun (Springer, 2025)
Introduction Although laparoscopic total extraperitoneal (TEP) procedure has gained wide acceptance for inguinal hernia repair, there is still debate on the optimal technique in patients with a history of previous radical prostatectomy (RP). We aimed to evaluate the feasibility and safety of laparoscopic TEP in patients with a previous history of RP using a propensity score case-match analysis. Methods This study included male patients undergoing laparoscopic TEP repair between 2013 and 2024. According to the RP status, patients were case-matched based on age, BMI, ASA score, site of hernia and the year of surgery. A total of 162 patients were matched in a 1:5 ratio. The RP and non-RP groups were compared with respect to perioperative outcomes. Results The RP and non-RP group included 27 and 135 patients, respectively. The rate ofconversion to transabdominal preperitoneal repair (11.1%) or open surgery (14.8%) was significantly higher in the RP group (p<0.001). The RP group had longer operative times (160±57 vs. 94±38, p<0.001). The postoperative complication rates (7.4% vs. 6%), postoperative pain scores, length of stay (1.6±0.9 vs 1.2±0.9 days), time to return to daily life (2.9±1.8 vs 2.6±3.0 days), readmission (3.7% vs 0.7%), long-lasting pain (14.8% vs. 11.8%) and recurrence (0% vs 3.2%) were similar in both groups (p>0.05). Conclusion Laparoscopic TEP inguinal hernia repair in patients with a history of RP is feasible and safe with a similar mor bidity profile but an increased conversion rate and operative time compared to those with no history of RP.
Keywords: Inguinal hernia; Laparoscopic TEP repair; Previous radical prostatectomy; Outcomes